Dry CO2–CO fluid as an important potential deep Earth solvent. Issue 5 (December 2016) - Simakin, A. G.; Salova, T. P.; Gabitov, R. I.; Isaenko, S. I.
Abstract: Transport properties of reduced carbonic fluid have been studied experimentally at P = 2 kbar and T  = 700–1000°C in internally heated pressure vessel (IHPV). Synthetic FeCO3 and natural siderite were used to generate fluid during experiments using a platinum double‐capsule technique. A natural CaTiSiO5 aggregate was placed into the inner capsule as an additional source of trace elements. The outer capsule was loaded with albite glass. No water was introduced to the system and oxygen fugacity was established near to graphite–oxygen (CCO) buffer due to transformation of FeCO3 into a magnetite aggregate during decarbonation to yield CO and CO2 . The carbonates decomposed during initial heating of the experiments, causing their some constituent components to be dissolved in and transferred by the fluid to the pore space of the albite glass matrix. After temperature reached 1000°C glass, the shards annealed and then melted, as evidenced by a vesiculated glass in the quench products. Micro‐Raman investigation of the fluid in bubbles in the albite glass in experiments with decomposition of natural siderite yielded CO–CO2 mixture where CO mole fraction was 0.15–0.16. We observe significant concentrations of Pt, Mn, P, and REE in the albite glass; in contrast, no Fe or Mg transfer was detected. LA‐ICP‐MS analysis of the albite glass product yielded the average Pt content of 2 ppm. Such high Pt signal came from Pt particles (100–500 nm in size), which were observed on the walls of the bubbles embedded in the glass. Olivines and aluminous spinel were observed in the Fe‐oxide aggregate, demonstrating transfer of SiO2 and Al2 O3 from the albite melt by the reduced carbonic fluid from the albite glass (large capsule). Our results demonstrate that dry CO–CO2 fluid can be important agents of dissolution and transport, especially for Pt and other metals. The data imply that metals are chiefly dissolved as carbonyl complexes.